Multiple agroecosystem services of forage legumes towards agriculture sustainability: An overview - Kumar, Rakesh; Yadav, M R; Arif, Mohd; Mahala, D M; Kumar, Dinesh; Ghasal, P C; Yadav, K C; Verma, R K (The Indian Journal of Agricultural Sciences, 2020)
Forage legumes are contributing in sustainable crop production apart from nutritional security to the livestock. Forage legumes are crucial for the nutritional security for mankind as they are integral component for increased availability of animal protein and product which has higher biological value compared to plant proteins. The inclusion of forage legumes in crop production systems is more useful as these can not only provide food and feed to animals but also improves soil productivity and act as soil-conserving components of agricultural and agroforestry systems. Production system as a whole and tremendous deficit of forage nutritious resources demand in particular to give some importance to the forage crops especially leguminous forages. Therefore, critical assessment is necessary for determining the direction and magnitude of change in agricultural management practice with inclusions of forage legume. Forage legumes have good capacity as a feed to promote sufficient quantities and qualities required for different productive animals. Therefore, these crops can contribute to achieving the objectives of sustainable food/ fodder and environmental security. Hence, inclusion of legumes forages in cropping system is inevitable in advancing soil sustainability and food and nutritional security without compromising the long-term soil fertility base of the soil resources. Rational soil management practices must involve forage legume-based rotations and intercropping considerations for restoring soil health, and soil sustainability should be given due emphasis. Besides, forage legumes can also provide a wide range of benefits such as restoration of soil fertility, nitrogen fixation and fertilizer saving, enhancement of soil biology and biodiversity, improving soil carbon sequestration and by neutralizing negative impact of climate change. This review summarizes the potential role of forage legume in animal nutrition, soil fertility building, nitrogen fixation, soil biology and biodiversity, carbon sequestration, climate change and other ecological services provided.